2010
DOI: 10.1002/ana.21939
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal B‐cell cytokine responses a trigger of T‐cell–mediated disease in MS?

Abstract: We propose that episodic triggering of abnormal B-cell cytokine responses mediates 'bystander activation' of disease-relevant proinflammatory T cells, resulting in new relapsing MS disease activity. Our findings point to a plausible mechanism for the long-recognized association between infections and new MS relapses, and provide novel insights into B-cell roles in both health and disease, and into mechanisms contributing to therapeutic effects of B-cell depletion in human autoimmune diseases, including MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
425
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 461 publications
(456 citation statements)
references
References 44 publications
20
425
2
5
Order By: Relevance
“…Several studies have shown that the B cells of patients with MS have defects in the balance of their cytokine expression, with a propensity for overproduction of inflammatory cytokines [e.g., lymphotoxin, tumor necrosis factor alpha (TNF-α), interleukin (IL)-6] and a deficit in production of anti-inflammatory cytokines (e.g., IL-10) [91][92][93]. In studies of patients with MS who underwent B-cell depletion, treatment resulted in Fig.…”
Section: B-cell Cytokines and B-cell/t-cell Interactions In Msmentioning
confidence: 99%
“…Several studies have shown that the B cells of patients with MS have defects in the balance of their cytokine expression, with a propensity for overproduction of inflammatory cytokines [e.g., lymphotoxin, tumor necrosis factor alpha (TNF-α), interleukin (IL)-6] and a deficit in production of anti-inflammatory cytokines (e.g., IL-10) [91][92][93]. In studies of patients with MS who underwent B-cell depletion, treatment resulted in Fig.…”
Section: B-cell Cytokines and B-cell/t-cell Interactions In Msmentioning
confidence: 99%
“…Recent evidence suggests that a subset of B cells has an active role in the etiology of MS and may potentiate activity of MS-promoting T cells [34]. Reports that administration of antibody Rituximab, which targets CD20 on B cells, is effective at treating MS corroborate this hypothesis [34,35].…”
Section: Ahsct Mechanism Of Action: the Immunosuppression Hypothesismentioning
confidence: 93%
“…Reports that administration of antibody Rituximab, which targets CD20 on B cells, is effective at treating MS corroborate this hypothesis [34,35]. Interestingly, alemtuzumab also substantially affects B-cell homeostasis, and the reconstitution of these cells contrasts dramatically with that of the T cells [36].…”
Section: Ahsct Mechanism Of Action: the Immunosuppression Hypothesismentioning
confidence: 94%
“…[15] Rituksimab, anti-CD20 monoklonal antikordur, dolaşımdaki B hücrelerini tüketir, bunun sonuçu olarak, CD4+ ve CD8+ T hücre yanıtlarını etkiler, bir olguda nöbet kontrolünde etkili olduğu bildirilmiştir. [16] Son zamanlarda bazı RE'li hastalarda veya ailerinde ikinci bir otoimmün hastalık görüldüğü bildirilmiştir. RE ve Behçet hastalığının birinci derece akrabalarda görülmesi, RE'nin diğer otoimmün hastalıklarla genetik bir yatkınlık paylaştığını düşündürmüştür.…”
Section: Introductionunclassified